Assessment of Variations in HAPS Scores, CaMK II Expression Levels, and Prognostic Outcomes Among AP Patients with Diverse Disease Severities - Yu L; Zhao H; Cheng Y; Fang Z (Journal of Multidisciplinary Healthcare)
Long Yu, Hong Zhao, Yongpeng Cheng, Zhijian Fang Department of Hepatobiliary Surgery, Liupanshui People’s Hospital, Liupanshui, Guizhou Province, 553000, People’s Republic of ChinaCorrespondence: Zhijian Fang, Email rfsk183@163.comObjective: To analyze the differences in Harmless Acute Pancreatitis Score (HAPS), serum Calcium/Calmodulin-dependent Protein Kinase II (CaMK II) expression, and prognosis among patients with acute pancreatitis (AP) of varying disease severities.Methods: A retrospective analysis was conducted on the clinical data of 103 patients with acute pancreatitis (AP) treated at our hospital between April 2022 and April 2024. According to the revised Atlanta classification and the International Consensus on Definitions (2012), patients were divided into Group A (59 cases, mild cases) and Group B (44 cases, severe cases). The HAPS score was calculated using relevant examination data obtained upon admission. Fasting venous blood samples (5 mL) were collected from all subjects on the morning of the second day after admission, and serum CaMK II expression levels were measured using a double-antibody sandwich method. Patients were followed up for three months from the date of admission to record local complications, systemic complications, and mortality. Receiver operating characteristic (ROC) curves were plotted to analyze the predictive value of HAPS scores and serum CaMK II levels for mild AP and patient prognosis.Results: HAPS scores and serum CaMK II levels were assessed at admission. Severe cases showed significantly higher HAPS and CaMK II levels vs mild (P< 0.05). ROC analysis demonstrated combined detection (AUC=0.902) outperformed individual markers (HAPS=0.827; CaMK II=0.773) in predicting mild AP. Both biomarkers progressively increased with complication severity (local < systemic < death, P< 0.05), showing predictive value (AUC> 0.6) for prognosis.Conclusion: HAPS scores and CaMK II expression levels in AP patients show a gradual increase with the severity of the disease, and both can serve as predictive indicators of disease severity and prognosis in AP patients. Moreover, combined detection of these indicators has a higher predictive efficiency than single-item detection.Keywords: disease severity, AP, HAPS score, CaMK II expression, prognosis differences